Value Judgements, Positivism and Utility Comparisons in Economics (Journal of Business Ethics, 2024)
The issue of interpersonal comparisons of utility is about the possibility (or not) of comparing the utility or welfare or the mental states in general, of different individuals. Embedded in the conceptual framework of utilitarianism, interpersonal comparisons were admissible in economics as part of the theoretical justification of welfare policies until the first decades of the twentieth century. Under the strong influence of the scientific philosophy of positivism as reflected in the works of early neoclassical economists and as epitomized by Lionel Robbins, utility comparisons were subsequently rejected as a value judgement. Robbins’ methodological stance is still prevalent among mainstream economists. Despite the explicit rejection of comparability by the majority of economists, interpersonal comparisons are necessary for many key policy issues, such as progressive taxation, social welfare policies, GDP-based welfare comparisons, cost–benefit analysis, and public goods provision. In this paper, the case of interpersonal utility comparisons is discussed as an illustrative example of the usefulness of the study of the role of value judgements, and generally of the interrelationship between ethics and economics. It is argued that the current tension between theory and policy practice might be resolved through the efforts of prominent economists and philosophers to challenge positivism, and especially its problematic treatment of value judgements and of ethical assumptions in general. The discussion also provides more strength to the view that policy makers and their economic advisers cannot avoid ethical questions in their analysis of the workings of the economic system